Analisis Forecasting Erratic Demand Dan Safety Stock Laptop Dan Notebook User (Studi Kasus Di PT Bank YXZ) (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
This research was conducted based on a case study with the objective of determining the prediction of demand and the factors causing the demand for laptops and notebooks at PT Bank YXZ. Quantitative approaches gained from historical data of erratic demand and qualitative methods obtained from the findings of surveys and interviews comprise the study methodology. It is common knowledge that the procurement procedure at PT Bank YXZ is lengthy due to challenges in estimating the number of requests and budget planning uncertainties. Thus, operational tasks inside the Work Units are impeded as a result of the user not receiving a laptop or notebook on time. In addition, the safety stock will have a significant impact on the fulfillment of laptop and notebook demand. An excessive amount of laptop and notebook safety supply will result in waste. Conversely, too little will result in a scarcity. This forecasting study and safety stock is anticipated to aid PT Bank YXZ in making procurement and budgetary decisions.